A review of evidence of glacially-induced faulting and seismic shaking in eastern Canada. (15th January 2020) - Brooks, Gregory R.; Adams, John
Abstract: Evidence of early postglacial, glacially-induced seismic activity should be abundant in eastern Canada, which was formerly covered by the Laurentide Ice Sheet during the late Wisconsinan Glaciation. This review identified only two 'probable' and at most nine 'possible' examples of glacially-induced faulting over an area of ∼4 million km 2, a far lower number than that expected from a long-term rate of background seismicity. The 'probable' sites are the Holy Grail scarp, Manitoba, and the series of faults buried in the sub-bottom of Round Lake, Ontario. The 'possible' nine glacially-induced faults include the Aspy fault, Nova Scotia, and Timiskaming East Shore fault, Ontario, but there is little published information on the other seven features. Despite this low number, the common occurrence of subaqueous mass transport deposits interbedded within or immediately overlying glaciolacustrine-glaciomarine deposits in many modern lake basins strongly hints at an elevated period of glacially-induced seismicity over widespread areas of eastern Canada. In southern Quebec, the age of these mass transport deposits suggests that glacially-induced earthquake activity began as early as about 13.5 ka cal BP, which corresponds to the time of local ice melt-back. This indicates that glacially-induced seismicity began at the time of local deglaciation in southern Quebec, rather then being delayed as existing fault instability models imply. It is anticipated that new candidate glacially-induced or younger faults will be identified in eastern Canada over the next decade or so because of the increasing availability of new high-resolution data imagery sources. Highlights: No confirmed early postglacial, glacially-induced faults in eastern Canada. Two probable and at most nine possible such faults are identified. Early postglacial mass transport deposits are present in many lake basins. Mass transport deposits may be evidence of elevated glacially-induced seismicity.